Recognizing and responding to normalization of deviance (John Wiley & Sons, Inc. : American Institute of Chemical Engineers, 2018)
"Contains guidelines to assist facilities in recognizing and addressing the phenomenon of normalization of deviation -Provides techniques for addressing normalized deviations and techniques to eliminate waste in all manufacturing processes -Describes methods for identifying normalized deviation as well as where to find deviations -Includes techniques to reduce operational normalization of deviance and to reduce organizational normalization of deviance Market description: Process safety professionals in all areas of manufacturing; Process safety consultants; Chemical engineering students; Certified safety professionals"-- Provided by publisher.
"One of a series of process safety guideline and concept books published by the Center for Cemical Process Safety (CCPS)"--Quoted from [series?] page.
Keywords: System failures (Engineering) -- Prevention.; Fault location (Engineering); Manufacturing processes -- Safety measures.; Chemical plants -- Safety measures.; Normalization of deviance (Industrial sociology); elektronické knihy; electronic books